Sex Disparity in Cord Blood FoxP3+ CD4 T Regulatory Cells in Infants Exposed to Malaria In Utero. (11th February 2017) - Prahl, Mary; Jagannathan, Prasanna; McIntyre, Tara I.; Auma, Ann; Wamala, Samuel; Nalubega, Mayimuna; Musinguzi, Kenneth; Naluwu, Kate; Sikyoma, Esther; Budker, Rachel; Odorizzi, Pamela; Kakuru, Abel; et al.
Abstract: Sex differences in the immune response and in infectious disease susceptibility have been well described, although the mechanisms underlying these differences remain incompletely understood. We evaluated the frequency of cord blood CD4 T cell subsets in a highly malaria-exposed birth cohort of mother-infant pairs in Uganda by sex. We found that frequencies of cord blood regulatory T cell ([Treg ] CD4 + CD25 + FoxP3 + CD127 lo/− ) differed by infant sex, with significantly lower frequencies of Tregs in female than in male neonates ( P = .006). When stratified by in utero malaria exposure status, this difference was observed in the exposed, but not in the unexposed infants.